Second Language Learning Theories 2019
DOI: 10.4324/9781315617046-1
|View full text |Cite
|
Sign up to set email alerts
|

Second Language Learning

Abstract: This paper argues that, on one hand, there are compelling theoretical reasons to believe that interlanguage (IL) grammars are both systematically and randomly variable, and that the relationship between the two types of variation is a complex one. At any one stage of IL development, some structures may be systematically variable, but at the same time the existence of forms in free variation creates conditions conducive to systematic variation "setting in" at a later stage of development. On the other hand, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
68
0
6

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(82 citation statements)
references
References 1 publication
0
68
0
6
Order By: Relevance
“…Indeed, in the 1990s a typical argument in resisting epistemological expansions was to remind the critics pressuring for a social reorientation that Second Language Acquisition's main interest lies with language and its development. For example, Mitchell and Myles () noted that evaluations of how useful a particular theory is for the study of L2 learning must ask whether it sufficiently addresses the linguistic development dimension. And as Gass (, p. 84) put it in her response to Firth and Wagner's () social critique, many in the field of SLA strongly felt that even when the data are conversational (or psycholinguistic or judgments of grammaticality, and so on), ‘the emphasis […] is on the language used and not on the act of communication’.…”
Section: Disciplinary Goals the Culprit?mentioning
confidence: 99%
“…Indeed, in the 1990s a typical argument in resisting epistemological expansions was to remind the critics pressuring for a social reorientation that Second Language Acquisition's main interest lies with language and its development. For example, Mitchell and Myles () noted that evaluations of how useful a particular theory is for the study of L2 learning must ask whether it sufficiently addresses the linguistic development dimension. And as Gass (, p. 84) put it in her response to Firth and Wagner's () social critique, many in the field of SLA strongly felt that even when the data are conversational (or psycholinguistic or judgments of grammaticality, and so on), ‘the emphasis […] is on the language used and not on the act of communication’.…”
Section: Disciplinary Goals the Culprit?mentioning
confidence: 99%
“…Based on the approach of teaching-learning, teachers' beliefs are divided into two types: traditional and constructivist (Mitchell & Myles, 2004). As for traditional beliefs, it means that teachers view their role as limited to delivering knowledge to the students in a clear, organized, and systematic way.…”
Section: Teaching Beliefsmentioning
confidence: 99%
“…All these measures intend to tackle such issues as what are the current trend of teaching approaches, methods and techniques, who and what is being taught and developed, and, most importantly, in whose interests (David, Olwen, Janis, Mary & Anne, 2003). Expectantly, if teachers lean toward perceiving their teaching ability in accordance to what beliefs and knowledge they possess, they are more likely to adopt new approaches and skills in their teaching practices (Mitchell & Myles, 2004). Several previous studies (Fullan & Hargreaves, 2002;Lau, 2006;Shang, 2010) have demonstrated that activities for teacher development can impact positively on teaching processes and outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…Strategi penulisan dalam penulisan akademik L2 (Nacera, 2010;Mitchell & Myles, 2004;Alameddine & Mirza, 2016) melibatkan 1. strategi metakognitif (perencanaan, pemantauan, peninjauan, evaluasi, melaporkan temuan, mengenali struktur esai), 2. Strategi kognitif (pengulangan, organisasi, meringkas, citra menggunakan, menyimpulkan, menyim-pang, menulis catatan, parafrase), 3.…”
Section: Menggunakanunclassified